Investigating the psychometric properties of PaRCADS—Parenting to Reduce Child Anxiety and Depression Scale in a Norwegian sample - Ytreland, Kristin; Ingul, Jo Magne; Lydersen, Stian; Yap, Marie Bee Hui; Sim, Wan Hua; Sund, Anne Mari; Bania, Elisabeth Valmyr (International journal of methods in psychiatric research, 2024)
Objectives Parents play a pivotal role in child development and several parental factors have been identified as risk or protective factors for childhood anxiety and depression. To assess and target these parental factors in interventions, there is a need for a comprehensive, easy‐to‐use instrument. Method This study aimed to investigate the psychometric properties of an adapted version of the Parenting to Reduce Child Anxiety and Depression Scale, PaRCADS(N) in a Norwegian community sample (N = 163) of parents of children aged 8–12 years. Results Our findings indicate that PaRCADS(N) has acceptable psychometric properties. These results are comparable to those of the original study of the PaRCADS in Australia. Conclusion Based on these results, we recommend that PaRCADS(N) can be utilized by health care workers as a tool for assessment and identification of parental practices related to child anxiety and/or depression to target relevant risk and protective factors in treatment and prevention.